Towards a pragmatics of non-fictional narrative truth: Gricean and relevance-theoretic perspectives - Berghoff, Robyn; Huddlestone, Kate (Stellenbosch Papers in Linguistics Plus, 2016)
From a linguistic perspective, ‘truth’ is undoubtedly a pragmatic notion, as the truth of an utterance is not determined solely by its linguistic meaning, but is dependent upon the context in which it is uttered. Although pragmaticists have devoted some theoretical attention to factual truth, truth that is not established through comparison with an observable external reality remains comparatively under-theorised. This paper focuses on a particular kind of truth that falls within this category, namely non-fictional narrative truth. “Narrative truth” is defined as a judgement of verisimilitude accorded to the meaning of a narrative as a whole. This narrative meaning is neither rationally nor empirically verifiable, but rather arrived at by a hermeneutic process. The paper argues that certain criteria previously identified as influencing hearers’ perceptions of testimony also contribute to the creation of an impression of narrative truth. It then examines the position of these criteria within Gricean and relevance-theoretic pragmatic accounts of interpretation. Using as an illustrative example a transcription of a testimony presented to South Africa’s Truth and Reconciliation Commission (TRC), the paper considers whether behaviour deemed ‘cooperative’ in typical conversational interaction is sufficient to yield an impression of a narrative’s truth in this particular domain. A principal finding is that adherence to the standard Gricean ‘recipe’ for cooperative conversational behaviour, with its prioritisation of truthfulness, fails to yield an impression of narrative truth. Relevance theory, on the other hand, which places equal emphasis on the form and content of utterances, more easily explains why the truth of certain kinds of narratives may be questioned. However, the criterion of relevance is also found to raise some complications, as what counts as ‘relevant’ differs across speakers and cultures. The paper concludes with a contemplation of the ethical issues raised when certain kinds of narrative are deemed ‘untruthful’ and remain figuratively unheard.